Volatile organic compounds (VOC) as biomarkers for detection of Ceratocystis platani. Issue 4 (16th June 2020) - Brilli, Federico; Luchi, Nicola; Michelozzi, Marco; Calamai, Luca; Cencetti, Gabriele; Pecori, Francesco; Nigrone, Emanuele; Santini, Alberto
Abstract: Ceratocystis platani causes canker stain of plane trees, and it represents a serious disease of Platanus spp. both in the United States and Europe. Current chemical or biological controls do not effectively manage C. platani, so new preventive methods need to be developed in order to limit this pathogen spreading. In this work, we have characterized the main volatile organic compounds (VOC) emitted in vitro from pure cultures of C. platani and other common pathogenic fungal species of hosts plants growing in the same ecosystems as plane trees. We found that C. platani emitted a similar blend of VOC compared with phylogenetically similar species C. populicola . In particular, C. platani was characterized by emission of isoamyl acetate and isobutyl acetate while C. populicola by ethyl acetate and isobutyl acetate, which were not released by any of the other out‐group fungal species grown on the same medium. Moreover, following a targeted approach based on the main VOC found in vitro, we have successfully validated in vivo that VOC uniquely emitted by C. platani (i.e. isobutyl acetate along with isoamyl alcohol) were released from the bark of plane trees following C. platani inoculation. Our results highlight the possibility to exploit VOC emitted specifically by C. platani as biomarkers to recognize Platanus x acerifolia plants infected by this pathogen.